PERTUMBUHAN Protocorm Like Bodies ANGGREK BULAN (Phaleonopsis amabilis (L.) Blume) PADA BERBAGAI KOMBINASI Benzil Amino Purine DAN Naphtalene Acetic Acid SECARA IN VITRO - Siti Mutmainah; Muslimin Muslimin; Dewi Wahyuni (Jurnal Warta Rimba, 2019)
The Moon Orchid (Phalaenopsis amabilis (L.) Blume) is one of the natural orchid species of the Orchidaceae family that is the conservation plant species because of its existence is threatened with extinction.One of the conservation efforts of orchid moon (Phaleonopsis amabilis (L.) Blume) is to perform the technique of orchid plant propagation generatively through seeds with plant breeding methods in vitro. This study aims to obtain a combination of Benzyl Amino Purine (BAP) and Naphthalene Acetic Acid (NAA) concentrations that can accelerate the growth of Protocorm Like Bodies orchid months. This research was conducted from January to March 2018, located at Tissue Culture Network Laboratory, Faculty of Forestry, Tadulako University, Palu. This research use Completely Random Design with advanced test of Honest Real Beda, where there are six treatments: M0 (control); M1 (MS + 0,5 ppm BAP + 03 ppm NAA); M2 (MS + 1,0 ppm BAP + 0,6 ppm NAA); M3 (MS + 1,5 ppm BAP + 0,9 ppm NAA); M4 (MS + 2,0 ppm BAP + 1,2 ppm NAA); M5 (MS + 2,5 ppm BAP + 1,5 ppm NAA). The results showed that the concentration of combination that can accelerate the growth of protocorm of orchid moon was found in the treatment of M4 (MS + 2,0 ppm BAP + 1,2 ppm NAA), where the emergence of shoots was 8,6 HST, with the number of shoots of 1,0 fruit, when the emergence of leaf 15 HST, the number of leaves as much as 1,18 pieces with protocorm live percentage of 100%.Keywords: Phaleonopsis amabilis (L.) Blume, Protocorm Like Bodies, Benzyl Amino Purine, Naphthalene Acetic Acid, in vitro.